1997
DOI: 10.1143/jjap.36.7769
|View full text |Cite
|
Sign up to set email alerts
|

Calixarene Electron Beam Resist for Nano-Lithography

Abstract: New electron beam (EB) resists made of calixarene resists are introduced. Typical sensitivities of calixarene resists range from 700 µ C/cm2 to 7 mC/cm2. High-density dot arrays with 15 nm diameter constructed using calixarene resist were easily delineated using a point EB lithography system. Our results suggest that the resolution limit of calixarene resists is dominated by a development process such as adhesion to a substrate rather than by the EB profile. Calixarene resists are resistant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Such water soluble calixarenes display interesting biological properties such as antiviral and anti-bacterial activity [30]. It is found that calixarene derivatives as resist materials are used for electron-beam lithography [31,32].…”
Section: Calixarenesmentioning
confidence: 99%
“…Such water soluble calixarenes display interesting biological properties such as antiviral and anti-bacterial activity [30]. It is found that calixarene derivatives as resist materials are used for electron-beam lithography [31,32].…”
Section: Calixarenesmentioning
confidence: 99%
“…We used the system under a probe current of 100 pA and an acceleration voltage of 30 kV. In the drawing, the address resolutions were 10 nm and 2.5 nm for ZEP520 and calixarene [14,15] resists, respectively. Development was carried out using the commercial developers ZED-N50 (MIBK+IPA) and ZEP-RD (xylene) for 210 sec and 180 sec for ZEP520 and calixarene, respectively.…”
Section: Eb-drawing System [7]mentioning
confidence: 99%
“…To overcome the trade-off relationships, molecular glasses have received much attention as a next-generation resist because of their small particle size and uniform molecular structure. 1-4 Fujita et al reported hexaacetate p-methylcalix [6]arena as the first negative-type molecular resist with B10 nm resolution by point irradiation of EB. [5][6][7] Ueda et al also reported a multicomponent, alkaline developable, negative-type photoresist composed of calixresorcin [4]arene, with 4,4¢-methylenebis[2,6-bis(hydroxymethyl)phenol] as a crosslinker and diphenyliodonium 9,10-dimethoxyanthracene-2-sulfonate as a photoacid generator (PAG), and they achieved a 150-nm resolution pattern.…”
Section: Introductionmentioning
confidence: 99%
“…1-4 Fujita et al reported hexaacetate p-methylcalix [6]arena as the first negative-type molecular resist with B10 nm resolution by point irradiation of EB. [5][6][7] Ueda et al also reported a multicomponent, alkaline developable, negative-type photoresist composed of calixresorcin [4]arene, with 4,4¢-methylenebis[2,6-bis(hydroxymethyl)phenol] as a crosslinker and diphenyliodonium 9,10-dimethoxyanthracene-2-sulfonate as a photoacid generator (PAG), and they achieved a 150-nm resolution pattern. 8,9 Thereafter, many negative-or positive-type molecular resist materials have been reported using various molecular glasses.…”
Section: Introductionmentioning
confidence: 99%